The Function of Figure of Speech in Literacy Writing Short Story of Junior High School Students - Meirina, Eka; Rokhman, Fathur; Yuniawan, Tommi (Universitas Negeri Semarang, 2022)
The short story material is contained in the competency standards and basic competencies, then contained in the national standardized school exam grids. One of the elements of a short story that affects the quality of the short stories whether it is interesting or not is a figure of speech. A figure of speech is included in one of the indicators that must be mastered by students in the 2013 curriculum. The purpose of this study is to describe the function of the figure of speech used in literacy writing short stories for junior high school students. This research uses a stylistic approach. The data were collected using the heuristic technique and note-taking technique. Data analysis was conducted using the hermeneutic technique. The data in this study are sentences that contain the figure of speech in the short story made by MTs NU Banat Kudus and MTs NU Nurul Huda students, collected by researchers. The source of data in this study is the short stories made by students of MTs NU Banat Kudus and MTs Nurul Huda Kudus. Based on the results of the study, the function of figure of speech used in the literacy writing short stories of junior high school students obtained 4 types of functions. These functions include the function of bringing a description to life, the function of evoking certain impressions and atmosphere, the function of emphasizing narrative and emotions, and the function of portraying a character's feelings. To streamline the presentation, only two data will be presented as examples of each of the functions of the figure of speech in the literacy writing a short story for junior high school students. The variation in the function of the figure of speech found in this study can be a material for further research.